POSTERS CAN INCREASE KNOWLEDGE ABOUT THE BENEFITS OF VITAMINS IN VEGETABLES AND FRUITS IN TEENAGER - yanuarti petrika; Martiasapira Martiasapira; Iman Jaladri (Ikatan Sarjana Gizi Indonesia (ISAGI), 2022)
Vegetables and fruit in adolescents are useful to support their growth and development and good nutritional status. Knowledge is an important factor for the formation of one’s actions. There are various kinds of counseling media that can be done, one of which is poster media. This study aims to analyze the effect of giving poster media on increasing nutritional knowledge of junior high school teenagers. Methods : This study was a pre-experimental design with a pretest-posttest one group design. The research subjects were teenagers at Al-Bayan Muara Pawan, Ketapang regency. A total of 114 samples. Data analysis using Wilcoxon to see the difference in the effect of giving media before and after being given poster media. Research Results : There isi a difference in knowledge about the benefits of vitamins in vegetables before and after being given nutrition education using poster media for adolescents and There is a difference in knowledge about the benefits of vitamins in fruit before and after being given nutrition education using poster media for adolescents at the Al- Bayan Muara Pawan Islamic Boarding Schol, Ketapang Regency. Research suggestion : For Educational Institutions Media Poster can be used by multiplaying and spreading the poster where students pass or often gather so that the knowledge of islamic boarding school students can increase not only junior high school teenagers and for other researchers can conduct further research on other variables such as pocket money, physical activity and consumption behavior and nutrition education for parents.